Peningkatan Keaktifan Belajar Mahasiswa melalui Pemberian Penguatan Positif dalam Gaya Kepemimpinan Partisipatif di IAKN Manado - Yolanda Palar (Institut Agama Kristen Negeri Manado, 2022)
The enjoyable, effective, creative, innovative, and active study is a form of study which accentuates the liveliness of students in a way to improve performance. Style and study method provide huge impact to the achievement of study goals. This research intends to describe the implementation of participatory leadership style, accompanied by the strengthening in improving the study liveliness. It applies the Class Action Survey method to A-Class students of Theology study programs in Institute of National Christian Religion - Manado. The data analysis technique applies Miles and Huberman model (2014), such as data condensation, data display, verification and conclusion. Based on the research in 2 cycles, results yielded are the improvement of study liveliness after the participatory leadership style are applied, accompanied by the strengthening in improving the study liveliness. On the early condition, the liveliness only reaches 20.27. Meanwhile, after being proceeded on cycle 1, there is improvement and reaches 45.45. On this stage, the amount of active students is rising. Improvement is also emerged in cycle 2, and it reaches 77.27% of active students. It shows that the 70% of achievement indicator has been achieved.